1986
DOI: 10.1037/0003-066x.41.12.1311
|View full text |Cite
|
Sign up to set email alerts
|

The changing face of American psychology: A report from the Committee on Employment and Human Resources.

Abstract: The past two decades have witnessed demographic, social, and economic changes that have affected the nature of psychology. The Committee on Employment and Human Resources of the American Psychological Association (APA), based on an examination of available data, identified six trends with major implications for psychology and the APA: changes in the specialization of new doctorate recipients in psychology, the quality of doctoral training, participation in the field by women and minorities, the employment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 14 publications
3
106
1
Order By: Relevance
“…Whereas the average age of neuropsychologists across time has been remarkably stable, gender representation has been perhaps even more remarkable for changing over time. In the 1980s, an APA Committee on Employment and Human Resources (Howard et al, 1986) framed psychology's impressive gender composition transition as the "feminization of psychology." As noted by Ostertag and McNamara (1991), whereas in 1950 only 14.8% of new psychology doctorates were awarded to women, by 1984 women received half of the psychology doctorates.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the average age of neuropsychologists across time has been remarkably stable, gender representation has been perhaps even more remarkable for changing over time. In the 1980s, an APA Committee on Employment and Human Resources (Howard et al, 1986) framed psychology's impressive gender composition transition as the "feminization of psychology." As noted by Ostertag and McNamara (1991), whereas in 1950 only 14.8% of new psychology doctorates were awarded to women, by 1984 women received half of the psychology doctorates.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, scientifically oriented members were concerned that the APA was no longer an organization with which they could identify. In fact, data indicated that many new PhDs in the experimental field were choosing not to join the APA, and experimental psychologists represented the largest proportion of those resigning from the Association (Howard et al, 1986). And as more and more specialized psychological organizations emerged, scientific psychologists within the APA feared that there would be no center of gravity for scientific psychology.…”
Section: Enduring Tensions Between Scientists and Practitionersmentioning
confidence: 99%
“…And a 1985 report by the APA Committee on Employment and Human Resources (Howard et al, 1986) offers data that substantiate this concern. The report indicated that ''those who were not employed in health-service-provider subfields represented 36% of APA Members and Fellows but 54% of those individuals resigning from the association'' (Howard et al, 1986(Howard et al, , p. 1325. The report also indicated a declining proportion of PhD graduates joining the APA, across nearly all subfields, but the lowest rates were among those in experimental, comparative, and physiological psychology.…”
Section: Scientists' Concernsmentioning
confidence: 99%